The Influence of Curriculum and Teacher Motivation on Students’ Learning Achievement - Tika Suri; Alhadi Yan Putra; Suherman Suherman (Journal of Social Work and Science Education, 2026)
This study aims to analyze the combined influence of curriculum implementation and teacher motivation on student learning achievement in State Junior High Schools within Sematang Borang District. Employing a quantitative descriptive method, data were collected via questionnaires, observation, and documentation from a sample of 70 principals and teachers across two schools: SMP Negeri 23 and SMP Negeri 60 Palembang. Analysis involved normality, linearity, and multicollinearity tests, followed by correlation, regression, t-tests, and an F-test. The results indicate a statistically significant joint influence, with curriculum and teacher motivation together explaining 59.6% of the variance in student achievement. The novelty lies in empirically examining the synergistic effect of these two factors within a specific Indonesian district context. Practically, the findings underscore the need for integrated school improvement policies that simultaneously enhance curricular delivery and teacher incentive structures. This research contributes to educational management theory by quantifying the collective impact of institutional and human resource variables on academic outcomes.